IFN-GAMMA SECRETION AND IL-10 AFTER STIMULATION OF ESAT-6-CFP-10 (EC610) FUSION ANTIGEN IN PATIENTS WITH ACTIVE TUBERCULOSIS AND LATENT TUBERCULOSIS - Prihantika S., Sabrina; Kurniati, Nova; Rahadiyanto, Kemas Ya'kub; Saleh, M Irsan; Hafy, Zen; Tanoerahardjo, Francisca Srioetami; Nugraha, Jusak; Salim, Eddy Mart (Biomedical Journal of Indonesia, 2019)
Tuberculosis (TB) is an infectious disease caused by the bacterium Mycobacterium tuberculosis which is still a health problem in the world including in Indonesia. TB infection arises due to interference with the regulation of the body's defense system. Cellular immune system plays a role in fighting TB infection, namely the role of T lymphocytes that differentiate into Th1 cells secrete pro-inflammatory cytokines IFN-? and Th2 cells that secrete IL-10 anti-inflammatory cytokines. The EC610 fusion antigen is specific and has a strong antigenicity to T cell stimulation. The aim of the study was to determine differences in the mean levels of IFN-? and IL-10 after EC610 antigen stimulation in patients with active TB and latent TB. The design of this study was a quasi-in vitro experiment with PBMC culture stimulated by EC610 antigens in the active TB and latent TB groups. The research and examination were carried out at the South Sumatra Province SSR and the Health Research and Development Laboratory Center, Central Jakarta. There were 21 subjects with active TB and 28 subjects with latent TB who met the inclusion criteria. Measurement of IFN-levels? and IL-10 was performed using ELISA-Reader. The results showed the levels of IFN-? and IL-10 after EC610 antigen stimulation were higher in active TB than latent TB. High levels of IFN-? active TB patients showed protective immune responses against M.tb germs while high levels of IL-10 showed their role as anti-inflammatory. There is no significant difference in the average level of IFN-? in patients with active TB and latent TB (p = 0.769) and there was a significant difference in the level of IL-10 levels after EC610 antigen stimulation was higher in active TB than latent TB (p = 0,000).